O uso da história da matemática nas produções do Programa de Desenvolvimento Educacional (PDE) do Paraná - Rhea, Vanessa Cristina (2018)
This research aims to analyse how the History of Mathematics has been covered in final articles produced by teachers who participated in the Educational Development Program (PDE) in the state of Parana - a program of continuing education for teachers. In order to do so, we selected the articles produced in the PDE in the field of mathematics that approached the History of Mathematics, which were produced by the classes and published in the PDE Journals from 2007 to 2010 and from 2012 to 2014. We obtained a total of 56 works, which were our study goal. Based on the analysis of content, we organized data into the following 5 categories: the authors of the articles, the subjects taking part in the research and topics covered, the theoretical reference on the History of Mathematics, the approach and the use of the History of Mathematics and, finally, the evaluation and the findings obtained in the articles. Concerning the characterization of the approach of the History of Mathematics, we are based on the possibilities proposed by Tzanakis and Arcavi in the chapter Integrating History of Mathematics in the classroom: an analytic survey from the book History in Mathematics Education (2000). Through the analysis, we observed that teachers use this teaching strategy in most cases to motivate a math class and to work on content that students usually have difficulties. It is common to use historical texts to introduce information, followed by problem solving, and also to stimulate students to carry out research on historical themes using the Internet. Although students participate actively in the classes and interact, showing interest in the activities, they do not always present satisfactory results when evaluated. Therefore this research indicates that teachers of basic education validate the use of the History of Mathematics as a teaching strategy for the implementation of their educational pedagogical works. This reinforces the importance of using the History of Mathematics in the classroom. However, other aspects still need to be explored so that it is effectively used as a teaching strategy